Desempenho e emissões de trator em semeadura com diferentes configurações de sulcadores em área com tráfego controlado de máquinas - Bertollo, Gilvan Moisés (2018)
To minimize the problem of soil compaction caused by the heavy traffic of machines on the soil an alternative is the controlled traffic, which performs the standardization of the wheel gauges of the machines and implements, allowing them to move in predetermined places. The objective of this study was to evaluate the traction performance and the engine gas emissions of an agricultural tractor in an area with controlled traffic of machines at different intensities, traction of a seeder equipped with three configurations opening of furrow. An agricultural area located in the county of Carazinho, RS. The experimental design was a randomized block 3 x 3, with three traffic situations (tractor traffic; tractor and harvester traffic; tractor, harvester and sprayer traffic). Furthermore, three opening of furrow configurations (double disc in all seeder lines; double disc on lines without traffic and furrow rod in those receiving the traffic; and double disc in non-contact tire lines with furrow rod in traffic lines). The variables analyzed were traction force, power in the traction drawbar, maximum power, speed, skidding of the driving wheels, operational capacity, engine efficiency. With the traction demand values, the corresponding torque in the dynamometer was applied to evaluate the hourly consumption, specific consumption and emissions of NO, NO2, NOx, CO2, O2 and particulates. It is concluded that the absence of furrower rod in the traffic lines reduces the power in the drawbar by 57.9% with tractor and harvester traffic and 53,5% with tractor, harvester and sprayer traffic. Traffic-free area, in relation to random traffic with double disc and double disc without furrow rod offer lower operational capacity, higher power provided by the engine and high engine utilization. The higher traffic intensity provides a 1.8% reduction in fuel consumption compared to the area without machine traffic. Controlled traffic at the highest intensity compared to the traffic-free area provided a reduction of 42.8% and 2.2% when using double disc, and 66.7% and 2.6% with double disc without furrow rod of particulate matter and nitrogen oxides, respectively. The non-cultivation of the area destined to traffic, represented in this study by 18.2%, reduced by 72.8%, 12.1%, 16.9% in traffic of the tractor and harvester, and 80%, 11.6%, 15% with the traffic of the tractor, harvester and sprayer the emission of particulates, nitrogen oxides and carbon dioxide, respectively, compared to the cultivation of these lines using furrow rod.